Practice of Sustainability in Higher Education - Ariesanti, Alia; Ganis Sukoharsono, Eko; Irianto, Gugus; Erwin Saraswati, Erwin (International Journal of Engineering and Technology, 2018)
Higher education have a significant role in supporting the realization of sustainable development, thus forming the concept of the sustainable university. The concept of the sustainable university emphasizes the importance of economic, environmental and social activities conducted by the college. The college is expected to formulate the curriculum, perform research and community service activities with the topic of sustainability. The purpose of this study was to assess the extent of higher education considering the environmental, social and economical in their activities. The respondents of this study are the head of a department in Ahmad Dahlan University, Indonesia. This study uses a mixed method approach. Quantitative data obtained using a questionnaire, then processed by using the compared group statistical test. Qualitative data obtained using interview, then processed by using data reduction, data display and conclusion and verification. The results of this survey suggest that the head of the departments had considered the aspect of sustainability in formulating the curriculum, implementation of research and community service activities. From the three points of the Tridharma, which is learning and curricula, research and community service, the departments give more attention to community service activities.Â Â